Numerical simulation of viscoelastic contraction flows - M. A. Alves (2003)
In this work we present numerical results obtained with a finite volume method for the creeping flow of viscoelastic fluids in both axisymmetric and planar 4: 1 contractions. Two theological equations are considered, namely the constant-viscosity Oldroyd-B and the shear-thinning Phan-Thien/Tanner (PTT) models. Accurate solutions are presented over a wide range of the Deborah number (a measure of the elasticity of the flow) extending the attainable values of previous studies [1]. Vortex enhancement was observed for the axisymmetric contraction, with both theological models, while for the planar contraction vortex enhancement is only observed for the shear-thinning PTT model. In the latter geometry, vortex reduction and the appearance of a small lip vortex is predicted for the constant-viscosity Oldroyd-B fluid.